Analysis Of Phytochemicals, Antioxidant And Antihyperlipidemic Activities Of Methanolic And Aqueous Extracts Of Various Parts Of Garcinia Mangostana - Manogaran, Manimegalai (2016)
Garcinia mangostana is a tropical plant found commonly in South East Asia. This plant possesses anti-inflammatory, antibacterial, antiulcer, antiseptic effects and showed prevention against oxidative damage of low-density lipoprotein cholesterol (LDL-C). The present study aimed to evaluate the antioxidant and antihyperlipidemic activities as well as phytochemical analysis of methanolic and aqueous extracts of various parts of leaves of G. mangostana, namely leaves, stem, bark, hull, petals, stalk, seed and flesh. The highest phenolic content was found in methanolic (41.74 ug GAE/g) and aqueous (11.29 ug GAE/g) extracts of leaves. Leaves extracts also showed highest flavonoid content of 31.80 ug GAE/g in methanolic and 19.48 ug GAE/g in aqueous extracts. For ferric reducing antioxidant power (FRAP), both methanolic and aqueous extracts of leaves showed most potent activity ofO.4S ± 0.01 urnol Fe2+/g and 0.39 ± 0.09 umol Fe2+/g respectively while u-mangostin possessed low FRAP activity compared to the extracts. Methanolic extract of stalk showed highest 2,2-diphenyl-l-picrylhydrazyl (DPPH) radical scavenging activity with ECso of 3.36 ± 0.52 ug/ml, while aqueous extract of leaves showed ECso of 3.21 ± 0.57 J.1g/mL compared to 0.- mangostin which had ECso of 4.03 ± 0.87 ug/ml., For 2,2- azinobis (3-ethyl- benzothiazolin-6-sulfate acid) (ABTS) radical scavenging activity, methanolic extract of stem and aqueous extract of leaves showed highest activity with ECso of 0.78 ± 0.45 J.1g/mL and 0.81 ± 0.37 ug/ml., respectively plus 0.mangostin had ECso of 2.88 ± 0.55 J.1g/mL.